Preparation method of high-performance hydrophobic polyvinyl alcohol composite film
By using ternary composite plasticizer and phenylatic acid for esterification and crosslinking, combined with toughening modifier, a high-performance hydrophobic polyvinyl alcohol composite film was prepared, which solved the tensile strength and toughness of the polyvinyl alcohol film. The problem of insufficient results enables efficient modification and precise preparation of the membrane, broadening its application prospects.
Patent Information
- Application Number
- CN202411597976.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The tensile strength and toughness of the existing polyvinyl alcohol films are insufficient, and there are problems such as low production capacity and difficulty in precise control of film thickness during the preparation process, which limits its application potential.
The ternary composite plasticizer (urea, magnesium chloride and magnesium nitrate) is used to plasticize polyvinyl alcohol, and then add phenylatic acid as a crosslinking agent for esterification reaction, combined with toughening modifiers such as carboxymethylcellulose Sodium and microcrystalline cellulose are prepared by combining chemical crosslinking and physical modification.
The hydrophobicity and mechanical properties of the polyvinyl alcohol film are significantly improved, the water resistance and packaging strength of the film are improved, the fresh preservation effect is enhanced, and the film thickness is accurately controlled through a multi-step process, which improves the preparation efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polyvinyl alcohol composite films, and in particular relates to a method for preparing a high-performance hydrophobic polyvinyl alcohol composite film. Background Art
[0002] Polyvinyl alcohol (PVA) has great potential for application in the field of pharmaceutical excipients due to its hydrophilicity, barrier properties, film-forming properties, low cost, cross-linking and biodegradability. In industrial environments, PVA is essential for the processing of polarizers, packaging, paper, fibers and adhesives. It is used as an adhesive in the wood and paper industries, and can also be used to make separation membranes. Since the mechanical properties of PVA film are soft and its water resistance is poor, its application is greatly limited and cannot meet the use requirements of PVA film in practical applications. Therefore, it is necessary to modify the PVA film, which can not only improve its application properties such as mechanical and water resistance, but also broaden its functions. The modification methods of PVA film can be divided into chemical cross-linking or grafting modification and physical modification, such as blending modification and nano-composite, according to the different reaction mechanisms or modes of action. Blending modification and nano-composite have simple steps and can easily expand the functionality of PVA film; chemical cross-linking modification can form a chemical bond cross-linked network between the polymer chains of PVA film, thereby significantly improving the mechanical properties, thermal stability and water resistance of PVA film.
[0003] Chemical crosslinking refers to the process of macromolecular chains being linked by chemical bonds to form a network or spherical structure of polymers. Chemical crosslinking can improve the performance of polymers. Polyvinyl alcohol has a large number of hydrophilic light groups in its molecules, and exhibits strong affinity for water during external dry and wet changes. To improve its water resistance, the hydroxyl groups in the PVA molecules must be masked. The hydroxyl groups on the PVA chains can be used to undergo chemical reactions and converted into water-resistant groups; or a crosslinking agent can be added to undergo a crosslinking reaction to re-form a new polymer.
[0004] Xu Zixuan et al. (Journal of Zhongkai University of Agriculture and Engineering, 2019, 32 (1): 17-22) prepared a series of citric acid-modified starch / polyvinyl alcohol composite films by solution casting. The results showed that citric acid and starch underwent esterification and cross-linking reaction, and citric acid-modified starch could improve the mechanical properties of the composite film, reduce the haze, hydrophilicity and water vapor permeability of the film, and improve the preservation effect of the film on mangoes. Zhong Le et al. (Packaging Engineering, 2019, 40 (15), 67-73) used stearic acid as a modifier, stearic acid-96 as an emulsifier, and polyethylene glycol-400 as a plasticizer to modify the polyvinyl alcohol film, and studied the preservation of prunes. The results showed that an ester bond was formed between stearic acid and polyvinyl alcohol, and the water resistance of the film was significantly improved. In addition, the preservation experiment found that compared with the blank group and PVA film group, the stearic acid / PVA group delayed the peak of the respiratory transition of prunes by 2 days, significantly reduced the mass loss rate of prunes, slowed down the change rate of soluble solid content, and extended the shelf life of prunes by 3.3 days. This shows that the use of stearic acid to modify polyvinyl alcohol can enhance the water resistance of the film, improve the packaging strength of the film, and enhance the preservation effect of the film. Lim et al. (Prog Org Coat, 2015, 85: 68-75) prepared five different cross-linked polyvinyl alcohol / boric acid hybrid films (PVA / BA) by solution blending. The results showed that the physical properties of PVA / BA hybrid films depend on the amount of BA added and the cross-linking density. With the increase of BA content, the size and number of PVA crystals decreased, while the cross-linking density increased, resulting in more compact molecular stacking and lower free volume in the amorphous region. With the increase of boric acid BA content (0-5%), the glass transition temperature and thermal stability of the film were greatly improved, and all the films showed good transparency.
[0005] Acetalization reaction can improve the properties of PVA, thereby obtaining products with good water resistance and mechanical properties. The water resistance of PVA film can be improved by using aldehydes such as formaldehyde, acetaldehyde, butyraldehyde, etc. to react with PVA for acetalization, or by using glyoxal, N-methylol urea, N-methylol melamine, N-methylol ethylene urea, etc. to react with PVA for cross-linking.
[0006] Zhang Li et al. (Functional Materials, 2020, 51 (4): 4153-4159) used glutaraldehyde and urea to crosslink polyvinyl alcohol, and added different types of plasticizers (propylene glycol, PEG-400, MgCl2) to destroy the hydrogen bonding of PVA and reduce its crystallinity, thereby achieving the plasticization modification effect. Luo Yafang et al. (Guangzhou Chemical Industry, 2018, 46 (24): 53-56) used electrospinning technology and glutaraldehyde as a post-crosslinking agent to explore the effect of glutaraldehyde concentration on the water resistance of PVA fiber film. The results show that after glutaraldehyde crosslinking treatment, the morphology of PVA fibers is not destroyed, the water resistance is significantly improved, and the change of glutaraldehyde concentration has little effect on the water resistance.
[0007] As a water-soluble polymer, polyvinyl alcohol is not only simple to prepare and low in cost, but also has excellent hydrophilicity, gas barrier properties, acid and alkali resistance and organic solvent resistance, as well as outstanding biosafety and good film-forming ability. Through modification processes such as esterification cross-linking, aldol condensation, compound plasticization, nano-reinforcement and blending hybridization, the mechanical and water resistance properties of polyvinyl alcohol film can be significantly improved, which greatly promotes the practical application of polyvinyl alcohol film. Despite this, at present, there are still some problems with the modified polyvinyl alcohol film, such as the tensile strength and toughness of the polyvinyl alcohol film. In addition, in terms of preparation, solution blending and cast molding are mainly used. Compared with the melt blending and blow molding methods of traditional packaging materials such as PP, PVC and PE, this method has the disadvantages of low production capacity and difficulty in accurately controlling film thickness. Summary of the invention
[0008] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a high-performance hydrophobic polyvinyl alcohol composite film. The polyvinyl alcohol composite film prepared by the method of the present invention has good hydrophobicity.
[0009] The present invention is achieved through the following technical solutions: A method for preparing a high-performance hydrophobic polyvinyl alcohol composite film comprises the following steps: 1) Plasticization of polyvinyl alcohol: Add polyvinyl alcohol and water into a reaction kettle, then add a plasticizer, heat and stir to react, and obtain a plasticized polyvinyl alcohol mixed solution; 2) Hydrophobic modification of polyvinyl alcohol: adding a crosslinking agent and an emulsifier to the polyvinyl alcohol mixed solution obtained in step 1), and performing an esterification reaction under constant temperature and stirring conditions to obtain a hydrophobically modified polyvinyl alcohol composite material; 3) Preparation of polyvinyl alcohol hydrophobic film: adding a toughening modifier to the polyvinyl alcohol composite material obtained in step 2) under stirring conditions of 80°C to 90°C, dispersing it evenly and then cooling it to room temperature, ultrasonically treating it to obtain a uniform and stable film solution, casting it into a film and then drying it to obtain a high-performance hydrophobic polyvinyl alcohol composite film; Wherein: the plasticizer in step 1) is a ternary complex of urea, magnesium chloride and magnesium nitrate; The cross-linking agent in step 2 is selected from pyromellitic acid.
[0010] In some embodiments, the mass ratio of urea, magnesium chloride and magnesium nitrate is 1:(0.5-2):(0.5-2), more preferably 1:1:1.
[0011] In some embodiments, the mass ratio of the plasticizer to the polyvinyl alcohol in step 1) is 1:1-20, more preferably 1:5-10.
[0012] In some embodiments, the emulsifier is selected from one or more of Tween-60, Tx-10, tristyrylphenol polyoxyethylene ether, tristyrylphenol polyoxyethylene ether, isomeric tridecanol polyoxyethylene ether, isomeric tridecanol polyoxyethylene ether, fatty alcohol polyoxyethylene ether and cardanol polyoxyethylene ether.
[0013] In some embodiments, the toughening modifier is one or both of sodium carboxymethyl cellulose and microcrystalline cellulose.
[0014] In some embodiments, the mass ratio of polyvinyl alcohol to water is 1:1-20, preferably 1:3-10.
[0015] In some embodiments, the heating temperature in step 1) is 60-100°C, more preferably 70-90°C.
[0016] In some embodiments, the heating and stirring reaction time of step 1) is 30 min-3 h, more preferably 1-2 h.
[0017] In some embodiments, the mass ratio of the cross-linking agent to the polyvinyl alcohol in step 2) is (0.5-2):1, more preferably (1-1.5):1.
[0018] In some embodiments, the mass ratio of the toughening modifier to the polyvinyl alcohol in step 3) is (0.5-2):1, more preferably (0.4-0.6):1.
[0019] On the other hand, the present invention provides a high-performance hydrophobic polyvinyl alcohol composite film, which is prepared by any of the methods described above.
[0020] Pure PVA film has the disadvantages of being brittle, having low elongation at break and poor water resistance. Plasticizers are often added to improve the mechanical properties and water resistance of PVA film. Commonly used plasticizers for PVA film are small molecule polyols, alcohol amines and amides. The mechanism of these small molecules plasticizing PVA is to form hydrogen bonds with the hydroxyl groups on the PVA molecular chain, reduce the hydrogen bonding within and between PVA molecules, thereby reducing the crystallinity of PVA and improving the thermoplastic processing properties of PVA. The effect of a single plasticizer is not ideal, so composite plasticizers are usually used to modify PVA.
[0021] The present invention has achieved the following beneficial effects: The ternary composite plasticizer used in the present invention can destroy the hydrogen bonding in the PVA molecules, reduce the crystallinity and melting point of the PVA, and has a significant plasticizing effect on the PVA. Compared with single plasticizers and binary plasticizers, the PVA film modified by the ternary composite plasticizer of the present invention has good hydrophobicity and excellent mechanical properties.
[0022] In order to further improve the mechanical properties of the PVA film, the present invention also adopts a chemical cross-linking method to modify the PVA film. The hydroxyl groups in the PVA molecules are masked by an esterification reaction between isophthalic acid and the hydroxyl groups of PVA, and cross-linking can be achieved, which can not only improve the hydrophobic properties of PVA, but also greatly enhance the mechanical properties of the PVA film.
[0023] The invention combines physical modification and chemical cross-linking modification, and the prepared PVA composite film has high hydrophobicity and good mechanical properties and has broad application prospects. DETAILED DESCRIPTION The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The endpoints and any values of the scope described in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.
[0025] Example 1 1) Plasticization of polyvinyl alcohol: by weight, add 10 parts of polyvinyl alcohol and 50 parts of water into a reactor, then add 2 parts of plasticizer, heat to 90°C, stir and react for 1 hour to obtain a plasticized polyvinyl alcohol mixed solution; 2) Hydrophobic modification of polyvinyl alcohol: 10 parts of pyromellitic acid and 0.5 parts of emulsifier Tween-60 were added to the polyvinyl alcohol mixed solution obtained in step 1), and an esterification reaction was carried out under reflux stirring for 1 hour to obtain a hydrophobically modified polyvinyl alcohol composite material; 3) Preparation of polyvinyl alcohol hydrophobic film: Add 4 parts of carboxymethyl cellulose and 2 parts of polydimethylsiloxane to the polyvinyl alcohol composite material obtained in step 2) under stirring at 80°C, disperse evenly and then cool to room temperature, perform ultrasonic treatment to obtain a uniform and stable film solution, cast into a film and then dry to obtain a high-performance hydrophobic polyvinyl alcohol composite film; Wherein: the plasticizer is a mixture of urea, magnesium chloride and magnesium nitrate in a mass ratio of 1:1:1.
[0026] Example 2 1) Plasticization of polyvinyl alcohol: by weight, add 10 parts of polyvinyl alcohol and 90 parts of water into a reactor, then add 3 parts of plasticizer, heat to 90°C, stir and react for 1 hour to obtain a plasticized polyvinyl alcohol mixed solution; 2) Hydrophobic modification of polyvinyl alcohol: 15 parts of pyromellitic acid and 0.5 parts of emulsifier Tween-60 were added to the polyvinyl alcohol mixed solution obtained in step 1), and an esterification reaction was carried out under reflux stirring for 1 hour to obtain a hydrophobically modified polyvinyl alcohol composite material; 3) Preparation of polyvinyl alcohol hydrophobic film: Add 5 parts of carboxymethyl cellulose and 1 part of polydimethylsiloxane to the polyvinyl alcohol composite material obtained in step 2) under stirring at 90°C, disperse evenly and then cool to room temperature, perform ultrasonic treatment to obtain a uniform and stable film solution, cast into a film and then dry to obtain a high-performance hydrophobic polyvinyl alcohol composite film; Wherein: the plasticizer is a mixture of urea, magnesium chloride and magnesium nitrate in a mass ratio of 1:1:1.
[0027] Example 3 1) Plasticization of polyvinyl alcohol: by weight, add 10 parts of polyvinyl alcohol and 80 parts of water into a reactor, then add 2 parts of plasticizer, heat to 90°C, stir and react for 1 hour to obtain a plasticized polyvinyl alcohol mixed solution; 2) Hydrophobic modification of polyvinyl alcohol: 10 parts of pyromellitic acid and 0.5 parts of emulsifier Tween-60 were added to the polyvinyl alcohol mixed solution obtained in step 1), and an esterification reaction was carried out under reflux stirring for 1 hour to obtain a hydrophobically modified polyvinyl alcohol composite material; 3) Preparation of polyvinyl alcohol hydrophobic film: Add 4 parts of carboxymethyl cellulose and 2 parts of polydimethylsiloxane to the polyvinyl alcohol composite material obtained in step 2) under stirring at 80°C, disperse evenly and then cool to room temperature, perform ultrasonic treatment to obtain a uniform and stable film solution, cast into a film and then dry to obtain a high-performance hydrophobic polyvinyl alcohol composite film; Wherein: the plasticizer is a mixture of urea, magnesium chloride and magnesium nitrate in a mass ratio of 1:0.5:2.
[0028] Example 4 1) Plasticization of polyvinyl alcohol: by weight, add 10 parts of polyvinyl alcohol and 80 parts of water into a reactor, then add 1 part of plasticizer, heat to 90°C, stir and react for 1 hour to obtain a plasticized polyvinyl alcohol mixed solution; 2) Hydrophobic modification of polyvinyl alcohol: 10 parts of pyromellitic acid and 0.5 parts of emulsifier Tween-60 were added to the polyvinyl alcohol mixed solution obtained in step 1), and an esterification reaction was carried out under reflux stirring for 1 hour to obtain a hydrophobically modified polyvinyl alcohol composite material; 3) Preparation of polyvinyl alcohol hydrophobic film: Add 4 parts of carboxymethyl cellulose and 2 parts of polydimethylsiloxane to the polyvinyl alcohol composite material obtained in step 2) under stirring at 80°C, disperse evenly and then cool to room temperature, perform ultrasonic treatment to obtain a uniform and stable film solution, cast into a film and then dry to obtain a high-performance hydrophobic polyvinyl alcohol composite film; Wherein: the plasticizer is a mixture of urea, magnesium chloride and magnesium nitrate in a mass ratio of 1:0.5:2.
[0029] Comparative Example 1 The method of Example 1 is referred to, except that the plasticizer is a mixture of urea and magnesium chloride in a mass ratio of 1:1.
[0030] Comparative Example 2 The method of Example 1 is referred to, except that the plasticizer is a mixture of urea and magnesium nitrate in a mass ratio of 1:1.
[0031] Comparative Example 3 The method of Example 1 is referred to, except that 10 parts of stearic acid are used instead of pyromellitic acid.
[0032] Example 5: Test of water vapor transmission rate: Select examples and comparative samples that are wrinkle-free, stain-free, pinhole-free, and have uniform thickness. Add 10 mL of deionized water into the permeable cup, and then gently put in a black sealing ring to prevent the sample from contacting the moisture at the bottom of the cup. Then put in the cut sample film, and then put in another black sealing rubber ring, and finally put in the white sealing ring and tighten the cup cover to ensure that the sample does not shake significantly. Place all assembled permeable cups in the corresponding chambers in the water vapor permeability tester, and check the water vapor permeability value after 12 hours. Test three times and take the average value. The water vapor permeability coefficient conversion formula is: WVP=WVTR×(d / ⊿p), Where: WVP——water vapor transmission coefficient, g.cm / cm 2 .s.pa; WVTR——Water vapor transmission value measured by the instrument, g / (m 2 ·day) The test results are as follows: Example 6: Mechanical properties test: The tensile strength of the composite film was measured using a servo high and low temperature controlled tensile testing machine. The tensile speed was 50 mm and 1 mm / S. Each sample should be tested five times and the calculated results were averaged.
[0033] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a high-performance hydrophobic polyvinyl alcohol composite film, comprising the following steps: 1) Plasticization of polyvinyl alcohol: Add polyvinyl alcohol and water into a reaction kettle, then add a plasticizer, heat and stir to react, and obtain a plasticized polyvinyl alcohol mixed solution; 2) Hydrophobic modification of polyvinyl alcohol: adding a crosslinking agent and an emulsifier to the polyvinyl alcohol mixed solution obtained in step 1), and performing an esterification reaction under constant temperature and stirring conditions to obtain a hydrophobically modified polyvinyl alcohol composite material; 3) Preparation of polyvinyl alcohol hydrophobic film: adding a toughening modifier to the polyvinyl alcohol composite material obtained in step 2) under stirring conditions of 80°C to 90°C, dispersing it evenly and then cooling it to room temperature, ultrasonically treating it to obtain a uniform and stable film solution, casting it into a film and then drying it to obtain a high-performance hydrophobic polyvinyl alcohol composite film; in: The plasticizer in step 1) is a ternary complex of urea, magnesium chloride and magnesium nitrate; The cross-linking agent in step 2 is selected from pyromellitic acid.
2. The preparation method according to claim 1, characterized in that: The mass ratio of urea, magnesium chloride and magnesium nitrate is 1:(0.5-2):(0.5-2).
3. The preparation method according to claim 2, characterized in that: The mass ratio of urea, magnesium chloride and magnesium nitrate is 1:1:
1.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the plasticizer to the polyvinyl alcohol in step 1) is 1:1-20.
5. The preparation method according to claim 1, characterized in that: The emulsifier is selected from one or more of Tween-60, Tx-10, tristyrylphenol polyoxyethylene ether, tristyrylphenol polyoxyethylene ether, isomeric tridecanol polyoxyethylene ether, isomeric tridecanol polyoxyethylene ether, fatty alcohol polyoxyethylene ether and cardanol polyoxyethylene ether.
6. The preparation method according to claim 1, characterized in that: The toughening modifier is one or both of sodium carboxymethyl cellulose and microcrystalline cellulose.
7. The preparation method according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol to water is 1:1-20.
8. The preparation method according to claim 1, characterized in that: The heating temperature of step 1) is 60-100°C; the heating and stirring reaction time of step 1) is 30min-3h.
9. The preparation method according to claim 1, characterized in that: The mass ratio of the cross-linking agent to the polyvinyl alcohol in step 2) is (0.5-2):1; the mass ratio of the toughening modifier to the polyvinyl alcohol in step 3) is (0.5-2):
1.
10. A high-performance hydrophobic polyvinyl alcohol composite film, characterized in that: It is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Water-resistant polyvinyl alcohol (PVA) film composition as well as fusion preparation method thereof
CN102234405A
Compounded plasticizer for thermoplastic processing and method for plasticizing polyvinyl alcohol
CN102532595A
Polyvinyl alcohol polarizing membrane and preparation method thereof
CN103744141A
Polyvinyl alcohol (PVA) film and preparation method thereof, and polaroid
CN104356569A
Composite modifier for starch / polyvinyl alcohol composite material
CN104788734A
Cited By
High-tension slurry suitable for matrix dispensing, diaphragm and preparation process
CN119965459A